Diterpenoid Compounds Isolated from Chloranthus oldhamii Solms Exert Anti-Inflammatory Effects by Inhibiting the IKK/NF-κB Pathway - Lin-Chieh Chiu (MDPI AG, 2021)
Chloranthus oldhamii Solms (CO) is a folk medicine for treating infection and arthritis pain but its pharmacological activity and bioactive compounds remain mostly uncharacterized. In this study, the anti-inflammatory compounds of C. oldhamii were identified using an LPS-stimulated, NF-κB-responsive RAW 264.7 macrophage reporter line. Three diterpenoid compounds, 3α-hydroxy-ent-abieta-8,11,13-triene (CO-9), 3α, 7β-dihydroxy-ent-abieta-8,11,13-triene (CO-10), and decandrin B (CO-15) were found to inhibit NF-κB activity at nontoxic concentrations. Moreover, CO-9 and CO-10 suppressed the expression of IL-6 and TNF-α in LPS-stimulated RAW 264.7 cells. The inhibitory effect of CO-9 on TNF-α and IL-6 expression was further demonstrated using LPS-treated bone marrow-derived macrophages. Furthermore, CO-9, CO-10, and CO-15 suppressed LPS-triggered COX-2 expression and downstream PGE2 production in RAW 264.7 cells. CO-9 and CO-10 also reduced LPS-triggered iNOS expression and nitrogen oxide production in RAW 264.7 cells. The anti-inflammatory mechanism of the most effective compound, CO-9, was further investigated. CO-9 attenuated LPS-induced NF-κB activation by reducing the phosphorylation of IKKα/β (Ser176/180), IκBα (Ser32), and p65 (Ser534). Conversely, CO-9 did not affect the LPS-induced activation of MAPK signaling pathways. In summary, this study revealed new anti-inflammatory diterpenoid compounds from C. oldhamii and demonstrated that the IKK-mediated NK-κB pathway is the major target of these compounds.